ANALISISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI ALJABAR MELALUI OBJEK LANGSUNG MATEMATIKA PADA SISWA KELAS VII SMP NEGERI 6 TONDANO - Niluh Norvi Natalia; Rosiah J. Pulukadang; Rosiah J. Pulukadang; Anekke Pesik; Derel F. Kaunang (Discovery, 2022)
Abstract: This research is motivated by problems encountered in mathematics learning in SMP Negeri 6 Tondano in algebraic operating materials. This research aims to find out the mistakes made by students in solving mathematical problems, especially in algebraic operating materials related to direct objects of mathematics. This type of research is descriptive research. The population of this study was 20 students. The data collection techniques in this study use test methods, interviews, and documentation. The results of this study show that the mistakes that students often make in solving algebraic operations problems are related to facts, concepts, operations, and principles. (a) Of the fact errors included in the medium category i.e. 42.5% (b) Of the concept errors included in the high category i.e. 63.125% (c) Of the operating errors included in the high category i.e. 65.625% (d) Of the principle errors included in the medium high category 48,125% Keywords: Error Analysis, Mathematical Direct Objects, Algebraic Operations